The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Encyclopedia of Environmental Microbiology 2003
DOI: 10.1002/0471263397.env134
|View full text |Cite
|
Sign up to set email alerts
|

Filamentous Bacteria in Activated Sludge: Current Taxonomic Status and Ecology

Abstract: Methods for the Detection of Filamentous Bacteria Involved in Sludge Bulking or Foaming Isolation and Cultivation of Filamentous Bacteria Involved in Sludge Bulking or Foaming Taxonomy of Filamentous Bacteria Causing Foaming and Bulking Problems in the Activated Sludge Process Filaments Affiliated with the β‐Subclass of the Proteobacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…belong to the CFB phylum. Although previous studies did report that at least three types of filaments that occurred in activated sludge belong to the CFB phylum (Kämpfer and Wagner, 2003), and two out of five filamentous strains isolated by Seviour et al (1997) were identified as Chryseobacterium-like organisms belonging to the CFB phylum -there was no definitive indication that the two strains detected in the DGGE were actually filaments. One strain of Brevundimonas vesicularis isolated from paper machine slime deposit was able to produce polysaccharide (Rättö et al, 2005), and one strain was able to synthesis PHA using acid-hydrolyzed sawdust as carbon source (Silva et al, 2007).…”
Section: Microbial Community Analysis By Dggementioning
confidence: 84%
“…belong to the CFB phylum. Although previous studies did report that at least three types of filaments that occurred in activated sludge belong to the CFB phylum (Kämpfer and Wagner, 2003), and two out of five filamentous strains isolated by Seviour et al (1997) were identified as Chryseobacterium-like organisms belonging to the CFB phylum -there was no definitive indication that the two strains detected in the DGGE were actually filaments. One strain of Brevundimonas vesicularis isolated from paper machine slime deposit was able to produce polysaccharide (Rättö et al, 2005), and one strain was able to synthesis PHA using acid-hydrolyzed sawdust as carbon source (Silva et al, 2007).…”
Section: Microbial Community Analysis By Dggementioning
confidence: 84%
“…More than 30 different morphotypes of these filamentous bacteria have been described (Eikelboom 1975), based on their morphological characteristics, but it is clear now that a single morphotype may contain several phylogenetically different bacteria (Kämpfer and Wagner 2002). Some of these filaments have been cultured and their phylogeny determined (Seviour and Blackall 1999; Kämpfer and Wagner 2002). Consequently, 16S rRNA targeted probes are now available for the in situ detection of some of these filaments using fluorescence in situ hybridization (FISH) (Kämpfer and Wagner 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these filaments have been cultured and their phylogeny determined (Seviour and Blackall 1999; Kämpfer and Wagner 2002). Consequently, 16S rRNA targeted probes are now available for the in situ detection of some of these filaments using fluorescence in situ hybridization (FISH) (Kämpfer and Wagner 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations